Growth hormone deficiency in adults with Cushing's disease. Issue 2 (March 2021) - Tritos, Nicholas A.
Abstract : Growth hormone deficiency (GHD) generally occurs in patients with Cushing's disease (CD) as a consequence of cortisol excess. Mass effect may contribute to the development of GHD in the minority of patients with CD due to corticotroph macroadenomas. Patients with CD in remission are at considerable risk of GH deficiency as a consequence of pituitary surgery or radiation therapy. The purpose of the present review is to summarize data on GH deficiency in adults with CD. Untreated GH deficiency is associated with increased visceral adiposity, decreased lean mass, bone mass, and exercise capacity, impaired linear growth (in children), dyslipidemia, insulin resistance and impaired quality of life. Evaluation and treatment of GHD should be considered in patients with CD in remission. Serum insulin-like growth factor I (IGF-I) can be helpful in the diagnosis of GHD among patients with multiple additional pituitary hormone deficiencies. The diagnosis of GHD generally requires dynamic testing, including insulin, glucagon or macimorelin stimulation. Growth hormone replacement may improve body composition, bone density, linear growth (in children), exercise capacity, dyslipidemia and quality of life. While generally safe, GH replacement requires careful monitoring to assure effectiveness and tolerance in treated patients.